Roto-molding composition
By using a composition of stabilized polyethylene and substantially unstable polyethylene, a rotomolded part with high surface roughness is prepared, which solves the problem of insufficient adhesion of polyurethane and achieves high adhesion and improved performance.
Patent Information
- Application Number
- CN202180014962.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-17
- Filing Date
- 2021-02-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-02-10
AI Technical Summary
The prior art is difficult to effectively adhere polyurethane to polyethylene, mainly due to the difference in polarity between the two, resulting in insufficient adhesion.
The adhesion of the polyurethane is improved by using a composition comprising stabilized polyethylene and substantially unstable polyethylene.
High adhesion to polyurethane is achieved, improving the performance of rotomolded parts, especially in applications where insulating layers or structural strength is required.
Abstract
Description
Technical Field
[0001] Compositions and methods for rotomoulding parts having improved adhesion to polar polymers are provided. Background Art
[0002] Rotational molding, also known as rotomolding, is a well-known process that is widely used to produce hollow plastic parts such as gasoline containers, trash cans, agricultural storage containers, septic tanks, and sporting goods such as kayaks. The process is performed by loading a charge of finely divided plastic resin into a mold "shell" and then rotating the mold (usually on two axes) while heating it to a temperature above the melting point of the plastic resin. The molten plastic flows through the mold cavity under the force generated by the rotation of the device. The rotation continues for a sufficient time for the molten plastic to cover the mold surface. The mold is then cooled to freeze the plastic into a solid state. The final stage of the molding cycle is the removal of the part from the rotomolding machine.
[0003] It will be appreciated that the rotomoulding process produces hollow parts, i.e. parts having an inner surface and an outer surface. For certain end uses, it is desirable to coat the inner surface - or even fill the hollow area - in order to provide an insulating layer or to improve structural strength or buoyancy. In particular, it is known to use polyurethane for such coating or filling. However, it is difficult to effectively attach polyurethane to polyethylene due to the difference in polarity of the two polymers. This problem can be addressed by treating the polyethylene to increase the surface polarity, but this is expensive. SUMMARY OF THE INVENTION
[0005] In some embodiments, disclosed herein are compositions and methods for providing rotomolded parts having an interior surface with high surface roughness. In these embodiments, improved adhesion to polyurethane is observed.
[0006] In one embodiment, there is provided a polyethylene composition comprising:
[0007] 1) 85 to 99 weight percent of a stabilized polyethylene having a melt index I2 of 0.5 to 10 g / 10 min as measured by ASTM D 1238 at 190°C using a 2.16 kg load; a density of 0.920 to 0.950 g / cc as measured by ASTM D792; and
[0008] 2) 15 to 1 wt. % of a substantially non-stabilized polyethylene having (i) a high load melt index I of 2 to 20 g / 10 min as measured by ASTM D 1238 at 190°C using a 21.6 kg load 21 ; (ii) a density of 0.950 to 0.965 g / cc as measured by ASTM D792; and (iii) an average particle size of 500 to 3000 microns.
[0009] Definition of terms
[0010] Except in the examples or where otherwise indicated, all numerical values or expressions used in the specification and claims involving the amount of ingredients, extrusion conditions, etc. should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification and the attached claims are approximate values that can vary according to the desired properties expected to be obtained in various embodiments. At least rather than attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should be interpreted at least in terms of the reported significant digits and by applying ordinary rounding techniques. The numerical values listed in the specific examples are reported as accurately as possible. However, any numerical value inherently contains certain errors that are necessarily caused by the standard deviations present in their respective experimental measurements.
[0011] It should be understood that any numerical range listed herein is intended to include all subranges contained therein. For example, a range of "1 to 10" is intended to include all subranges between and including the listed minimum value of 1 and the listed maximum value of 10; that is, having a minimum value equal to or greater than 1 and a maximum value equal to or less than 10. Since the disclosed numerical ranges are continuous, they include every value between the minimum and maximum values. Unless expressly stated otherwise, the various numerical ranges specified in this application are approximate.
[0012] All composition ranges expressed herein are limited to and do not exceed 100% (volume % or weight %) in total in practice. When multiple components may be present in the composition, the sum of the maximum amounts of the individual components may exceed 100%, it being understood and as readily understood by those skilled in the art, the amounts of the components actually used will adhere to a maximum of 100%.
[0013] For a more complete understanding of the present disclosure, the following terms are defined and should be used in conjunction with the drawings and throughout the description of the various embodiments.
[0014] The term "monomer" as used herein refers to a small molecule that can chemically react and chemically bond with itself or other monomers to form a polymer.
[0015] As used herein, the term "alpha-olefin" is used to describe monomers having a linear hydrocarbon chain containing from 3 to 20 carbon atoms and having a double bond at one end of the chain; examples include butene-1; hexene-1 and octene-1.
[0016] Description of the implementation plan
[0017] A. Polyethylene
[0018] Polyethylene is a common plastic resin used to make rotomoulded parts. Polyethylene copolymers (which are usually made by mixing ethylene with C 4-10 Conventional polyethylenes are made by copolymerization of alpha-olefins in the presence of chromium catalysts or Ziegler Natta catalysts), although it is also known to use polyethylene homopolymers. The alpha-olefin comonomer produces "short chain branches" (SCBs) in the copolymer. These SCBs reduce the crystallinity of the copolymer (compared to linear ethylene homopolymers), and the copolymers generally have improved impact resistance compared to the homopolymers. These conventional polyethylenes may be referred to as "heterogeneous" in the sense that the polyethylene is actually a mixture of different polyethylene chains with significantly different molecular weights and comonomer distributions. Most notably, conventional heterogeneous polyethylenes generally contain three fractions:
[0019] i) a low molecular weight fraction with a high comonomer content (or high level of SCB) – this fraction is often referred to as “wax” or “extractables”;
[0020] ii) a very high molecular weight fraction with little or no comonomer - this fraction is often referred to as a "homopolymer"; and
[0021] iii) The fraction of intermediate molecular weight and SCB content.
[0022] These conventional polyethylenes are well suited for rotational molding. For example, while not wishing to be bound by theory, it has been speculated that the high molecular weight "homopolymer" fraction may enhance the stiffness or modulus of the rotationally molded part.
[0023] More recently, homogeneous polyethylenes have become commercially available. These homogeneous polyethylenes have a uniform (or narrow) molecular weight distribution and a uniform comonomer distribution. This in turn allows the homogeneous polyethylene to have a well-defined melting point (compared to heterogeneous polyethylenes having a melting point "range" or even multiple melting points). It is also known to use "homogeneous" polyethylene in rotational molding processes.
[0024] Stabilized Polyethylene
[0025] The term "stabilized polyethylene" broadly refers to polyethylene (which may be a heterogeneous polyethylene or a homogeneous polyethylene) that contains a "stabilizer" package to protect the polyethylene from degradation / oxidation during the roto-molding process. Generally speaking, any stabilizer package currently used for roto-molding applications is potentially suitable for use in the present process. The skilled artisan will recognize that many such stabilizer packages are currently in use.
[0026] In one embodiment, the stabilizer kit comprises:
[0027] 1) primary antioxidants (although not wishing to be bound by theory, they are generally believed to act to scavenge free radicals);
[0028] 2) Secondary antioxidants (although not wishing to be bound by theory, these are generally believed to act to quench hydroperoxides).
[0029] Suitable (non-limiting) examples of primary antioxidants include hindered phenols; hydroxylamines and lactones, and suitable amounts are 100 to 2000 (especially 250 to 1500) parts per million ("ppm") by weight based on the weight of the polyethylene.
[0030] Suitable (non-limiting) secondary antioxidants include phosphites and phosphinites, particularly in amounts of 100 to 2000 (especially 250 to 1500 ppm).
[0031] It is also desirable to include a hindered amine light stabilizer (HALS) in the rotomoulding composition, particularly in an amount of 500-3000 ppm. The optional additional use of zinc oxide (in an amount of 500 to 5000 parts per million by weight) and or ultraviolet (UV) absorbers can further improve the stability of rotomoulded parts exposed to sunlight.
[0032] In one embodiment, the stabilizer kit comprises:
[0033] 1) 250 to 1500 ppm of at least one primary antioxidant selected from:
[0034] 1.1) hindered phenols; and
[0035] 1.2) Hydroxylamine; and
[0036] 2) 100 to 1000 ppm of at least one secondary antioxidant selected from:
[0037] 2.1) phosphites; and
[0038] 2.2) phosphites; and
[0039] 3) 500 to 3000 ppm HALS; and
[0040] 4) 0 to 5000 ppm zinc oxide.
[0041] Many other additives are also known for use with polyethylene. Some of these additives are described in the Additives section below.
[0042] Additives can be incorporated into polyethylene compositions using mixing equipment such as an extruder or an internal batch mixer (also known as a Banbury mixer). Additives can be added "neat" (i.e., directly to the resin); as a "masterbatch" (i.e., by premixing the additive with a small amount of polyethylene and subsequently mixing with the bulk of the composition); or as a "premix" (i.e., a mixture of additives).
[0043] In some embodiments, the stabilized high density polyethylene composition is ground into a powder before being used in the rotational molding process (this is a common practice in the rotational molding process). The suitable (non-limiting) average particle size of the powder is 200 to 400 microns. In one embodiment, the average particle size of the stabilized polyethylene is lower than / smaller than the average particle size of the substantially non-stabilized polyethylene.
[0044] additive
[0045] In one embodiment, the rotomoulding composition may contain:
[0046] A) at least one primary antioxidant selected from
[0047] A.1) hindered phenols (non-limiting examples of which are described in Sections 1.1 and 1.4 below); and
[0048] A.2) hydroxylamine (non-limiting examples of which are described in Section 5 below);
[0049] B) at least one secondary antioxidant selected from phosphites and phosphonites (non-limiting examples of which are described in Section 4 below); and
[0050] C) at least one hindered amine light stabilizer "HALS" (non-limiting examples of which are described in Section 2.6 below).
[0051] Many other additives may also be included in the polyethylene composition used in the rotomoulding process. Some of these additives are briefly described below.
[0052] 1. Antioxidants (also called "hindered phenols")
[0053] 1.1 Alkylated monophenol
[0054] For example, 2,6-di-tert-butyl-4-methylphenol; 2-tert-butyl-4,6-dimethylphenol; 2,6-di-tert-butyl-4-ethylphenol; 2,6-di-tert-butyl-4-n-butylphenol; 2,6-di-tert-butyl-4-isobutylphenol; 2,6-dicyclopentyl-4-methylphenol; 2-(α-methylcyclohexyl)-4,6-dimethylphenol; 2,6-di-octadecyl-4-methylphenol; 2,4,6,-tricyclohexylphenol; 2,6-di-tert-butyl-4-methoxymethylphenol; and vitamin E.
[0055] 1.2 Alkyl hydroquinone
[0056] For example, 2,6-di-tert-butyl-4-methoxyphenol; 2,5-di-tert-butylhydroquinone; 2,5-di-tert-amyl-hydroquinone; and 2,6-diphenyl-4-octadecyloxyphenol.
[0057] 1.3 Hydroxylated diphenyl thioether
[0058] For example, 2,2'-thio-bis-(6-tert-butyl-4-methylphenol); 2,2'-thio-bis-(4-octylphenol); 4,4'-thio-bis-(6-tert-butyl-3-methylphenol); and 4,4'-thio-bis-(6-tert-butyl-2-methylphenol).
[0059] 1.4 Alkylene-bisphenols (also known as "hindered phenols")
[0060] For example, 2,2'-methylene-bis-(6-tert-butyl-4-methylphenol); 2,2'-methylene-bis-(6-tert-butyl-4-ethylphenol); 2,2'-methylene-bis-(4-methyl-6-(α-methylcyclohexyl)phenol); 2,2'-methylene-bis-(4-methyl-6-cyclohexylphenol); 2,2'-methylene-bis-(6-nonyl-4-methylphenol); 2,2'-methylene-bis-(6-nonyl- 4-methylphenol); 2,2'-methylene-bis-(6-(α-methylbenzyl)-4-nonylphenol); 2,2'-methylene-bis-(6-(α,α-dimethylbenzyl)-4-nonyl-phenol); 2,2'-methylene-bis-(4,6-di-tert-butylphenol); 2,2'-ethylene-bis-(6-tert-butyl-4-isobutylphenol); 4,4'-methylene-bis-(2,6-di-tert-butylphenol); 4,4' -Methylene-bis-(6-tert-butyl-2-methylphenol); 1,1-bis-(5-tert-butyl-4-hydroxy-2-methylphenol)butane, 2,6-di-(3-tert-butyl-5-methyl-2-hydroxybenzyl)-4-methylphenol; 1,1,3-tris-(5-tert-butyl-4-hydroxy-2-methylphenyl)butane; 1,1-bis-(5-tert-butyl-4-hydroxy-2-methylphenyl)-3-dodecylmercaptobutane; ethylene glycol-bis- (3,3,-bis-(3'-tert-butyl-4'-hydroxyphenyl)-butyrate)-di-(3-tert-butyl-4-hydroxy-5-methylphenyl)-dicyclopentadiene; di-(2-(3'-tert-butyl-2'-hydroxy-5'methylbenzyl)-6-tert-butyl-4-methylphenyl) terephthalate; and other phenolics, such as monoacrylates of bisphenols, such as ethylene bis-2,4-di-tert-butylphenol monoacrylate.
[0061] 2. UV absorbers and light stabilizers
[0062] 2.1 2-(2'-Hydroxyphenyl)-benzotriazole
[0063] For example, 5'-methyl-, 3'5'-di-tert-butyl-, 5'-tert-butyl-, 5'(1,1,3,3-tetramethylbutyl)-, 5-chloro-3',5'-di-tert-butyl-, 5-chloro-3'-tert-butyl-5'-methyl-3'-sec-butyl-5'-tert-butyl-, 4'-octyloxy, 3',5'-di-tert-pentyl-3',5'-bis-(α,α-dimethylbenzyl)-derivatives.
[0064] 2.2 2-Hydroxybenzophenone
[0065] For example, 4-hydroxy-4-methoxy-, 4-octyloxy-, 4-decyloxy-, 4-dodecyloxy-, 4-benzyloxy-, 4,2',4'-trihydroxy- and 2'-hydroxy-4,4'-dimethoxy derivatives.
[0066] 2.3 Hindered Amine Light Stabilizers (HALS)
[0067] For example, bis(2,2,6,6-tetramethylpiperidinyl)-sebacate; bis-5-(1,2,2,6,6-pentamethylpiperidinyl) sebacate; n-butyl-3,5-di-tert-butyl-4-hydroxybenzylmalonate bis(1,2,2,6,6,-pentamethylpiperidinyl); condensation product of 1-hydroxyethyl-2,2,6,6-tetramethyl-4-hydroxy-piperidine and succinic acid; N,N'-(2,2,6,6-tetramethylpiperidinyl)-hexamethylenediamine and 4-tert-octylamino-2,6-dichloro-1,3,5-s -triazine condensation products; tris-(2,2,6,6-tetramethylpiperidinyl)-nitrilotriacetate, tetrakis-(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4butane-tetra-arbonicacid; and 1,1'-(1,2-ethanediyl)-bis-(3,3,5,5-tetramethylpiperazinone). These amines, commonly referred to as HALS (hindered amine light stabilizers), include 2,2,6,6-tetramethylpiperidinol butanetetracarboxylate. Such amines include hydroxylamines derived from hindered amines, such as bis(1-hydroxy-2,2,6,6-tetramethylpiperidin-4-yl)sebacate; 1-hydroxy-2,2,6,6-tetramethyl-4-benzoyloxypiperidine; 1-hydroxy-2,2,6,6-tetramethyl-4-(3,5-di-tert-butyl-4-hydroxyhydrocinnamoyloxy)-piperidine; and N-(1-hydroxy-2,2,6,6-tetramethyl-piperidin-4-yl)-ε-caprolactam.
[0068] 3. Phosphites and phosphonites
[0069] For example, triphenyl phosphite; diphenyl alkyl phosphates; phenyl dialkyl phosphates; tri(nonyl-phenyl) phosphite; trilauryl phosphite; tri(octadecyl) phosphite; distearyl pentaerythritol diphosphite; tri(2,4-di-tert-butylphenyl) phosphite; diisodecyl pentaerythritol diphosphite; 2,4,6-tri-tert-butylphenyl-2-butyl-2-ethyl-1,3-propanediol phosphite; bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, tristearyl sorbitol triphosphite; and tetrakis(2,4-di-tert-butylphenyl) 4,4'-biphenylene diphosphonite.
[0070] 4. Peroxide scavengers
[0071] For example, esters of β-thiodipropionic acid, such as the lauryl, stearyl, tetradecyl or tridecyl esters; zinc salts of mercaptobenzimidazole or 2-mercaptobenzimidazole; zinc dibutyldithiocarbamate; dioctadecyl disulfide; and pentaerythritol tetrakis-(β-dodecylmercapto)-propionate.
[0072] 5. Hydroxylamine and amine oxides
[0073] For example, N,N-dibenzylhydroxylamine; N,N-diethylhydroxylamine; N,N-dioctylhydroxylamine; N,N-dilaurylhydroxylamine; N,N-ditetradecylhydroxylamine; N,N-dihexadecylhydroxylamine; N,N-dioctadecylhydroxylamine; N-hexadecyl-N-octadecylhydroxylamine; N-heptadecyl-N-octadecylhydroxylamine; and N,N-dialkylhydroxylamines derived from hydrogenated tallow amine. Similar amine oxides (as disclosed in USP 5,844,029, Prachu et al.) are also suitable.
[0074] 6. Nitrones
[0075] For example, N-benzyl-α-phenylnitrone; N-ethyl-α-methylnitrone; n-octyl-α-heptylnitrone; N-lauryl-α-undecylnitrone; N-tetradecyl-α-tridecylnitrone; N-hexadecyl-α-pentadecylnitrone; N-octadecyl-α-heptadecylnitrone; N-hexadecyl-α-heptadecylnitrone; N-octadecyl-α-pentadecylnitrone; N-heptadecyl-α-heptadecylnitrone; N-octadecyl-α-hexadecylnitrone; and nitrones derived from N,N-dialkylhydroxylamines derived from hydrogenated tallow amine.
[0076] 7. Alkaline stabilizer
[0077] For example, melamine; polyvinyl pyrrolidone; dicyandiamide; triallyl cyanurate; urea derivatives; hydrazine derivatives; amines; polyamides; polyurethanes; alkali metal salts and alkaline earth metal salts of higher fatty acids, such as calcium stearate, calcium stearoyl lactylate, calcium lactate, zinc stearate, magnesium stearate, sodium ricinoleate and potassium palmitate; antimonypyrocatecholate or zinc pyrocatecholate, including neutralizing agents such as hydrotalcite and synthetic hydrotalcite; and Li, Na, Mg, Ca, Al hydroxycarbonates.
[0078] 8. Nucleating Agent
[0079] For example, 4-tert-butylbenzoic acid; adipic acid; diphenylacetic acid; sodium salt of methylene bis-2,4-dibutylphenyl; cyclic phosphate esters; sorbitol tribenzaldehyde acetal; and sodium salt of bis(2,4-di-tert-butylphenyl) phosphate or sodium salt of ethylene bis(2,4-di-tert-butylphenyl) phosphate. Nucleating agents can improve the stiffness of rotomoulded parts.
[0080] 9. Fillers and reinforcements
[0081] For example, calcium carbonate; silicates; glass fibers; asbestos; talc; kaolin; mica; barium sulfate; metal oxides and hydroxides; carbon black and graphite.
[0082] 10. other
[0083] For example, plasticizers; epoxidized vegetable oils, such as epoxidized soybean oil; lubricants; emulsifiers; pigments; fluorescent brighteners; flame retardants; antistatic agents; blowing agents and thiosynergists, such as dilauryl thiodipropionate or distearyl thiodipropionate.
[0084] Basic unstabilized polyethylene
[0085] The term "substantially non-stabilized" means that the polyethylene is susceptible to oxidation during the rotomoulding process. This can be confirmed after the rotomoulding process by observing the formation of oxide species (especially carbonyl groups) on the inner surface of the rotomoulding part. Oxide species can be detected using conventional Fourier transform infrared ("FTIR") instrumentation.
[0086] As a general guideline, the substantially non-stabilized polyethylene should contain less than 100 ppm of primary and / or secondary antioxidants, and may be free of any primary or secondary antioxidants. In one embodiment, the substantially non-stabilized polyethylene is free of any primary or secondary antioxidants.
[0087] In some embodiments, the substantially non-stabilized polyethylene has a very low flow rate. The flow rate is determined by measuring the amount of polymer that will flow through a capillary at a specified temperature and load. ASTM D1238 is used to measure flow rate. In one embodiment, when a 2.16 kg load is used in ASTM D1238 (at 190° C.), the non-stabilized polyethylene does not have a meaningful / measurable flow rate. The "high load" flow rate using a 21.6 kg load is 2 to 20 grams / 10 minutes or, for example, 3 to 6 grams / 10 minutes. Flow rate is also often referred to as a "melt index".
[0088] In one embodiment, the substantially non-stabilized polyethylene is produced using a heterogeneous catalyst, such as a Ziegler-Natta catalyst or a chromium catalyst.
[0089] Inner surface of molded parts
[0090] While not wishing to be bound by theory, it is believed that rotomoulded parts produced by this method have an outer surface made predominantly of stabilised polyethylene (as described above), and that substantially non-stabilised polyethylene tends to be located away from the outer surface (particularly on the inner surface).
[0091] In one embodiment, the inner surface of the part has a higher surface roughness than the outer surface. Surface roughness can be measured with a mechanical or optical profilometer. We have measured the roughness of the inner surface of parts made by the present method using a laser confocal microscope (a type of optical profilometer) and observed an average surface roughness "Ra" of greater than 10 microns. In contrast, the outer surface has been observed to have a much lower surface roughness - for example, Ra of 2 to 4 microns.
[0092] Additionally, we have observed the presence of carbonyl groups on the interior surface and, while not wishing to be bound by theory, we believe that these carbonyl groups are formed from oxidation of the substantially non-stabilized polyethylene.
[0093] We have carried out adhesion tests (described in the Examples) to measure the strength of the bond between rotomoulded part surfaces in a polyurethane layer. These tests have shown that a high strength bond is formed when the surfaces of the rotomoulded parts have both a) high surface roughness; and b) carbonyl groups.
[0094] B. Roto-molding method
[0095] As mentioned above, rotational molding is a well-known process that is performed by loading a charge of finely divided plastic resin into a mold "shell" and then rotating the mold (usually on two axes) while heating it to a temperature above the melting point of the plastic resin. The molten plastic flows through the mold cavity under the action of the force generated by the rotation of the device. The rotation continues for a sufficient time for the molten plastic to cover the mold surface. The mold is then cooled to freeze the plastic into a solid. The final stage of the molding cycle is to remove the part from the rotational molding machine.
[0096] The time required to complete a molding cycle depends on the bulk properties of the plastic being molded; the size of the molded part and the molding temperature. In addition, the plastic resin loaded into the mold is preferably finely divided (i.e. ground into a powder) and has a high bulk density and a narrow particle size distribution to promote "free flow" of the resin.
[0097] It is also recognized that the physical properties of the rotomoulded part are affected by using the appropriate molding cycle time, with "undercooked" parts having poor strength properties, while "overcooked" parts have poor appearance ("burnt" color) and / or degraded strength properties. It is desirable to have a short molding cycle (in order to improve the productivity of expensive rotomoulding machinery) and a wide "processing window" (i.e., the rotomoulding composition ideally provides a "properly cooked" part in a short period of time, but does not become "overcooked" over an extended period of time).
[0098] In addition, the properties of rotomoulded parts are influenced by the molecular structure of the polymer used to make the part. Important physical properties include stiffness (as represented by the modulus of the part), environmental stress crack resistance (or "ESCR"), impact resistance, and warpage resistance.
[0099] Therefore, the molding time and temperature of the method are affected by many variables. Specific / preferred conditions will also be affected by the choice of machine. However, those skilled in the art will be able to optimize the conditions without unnecessary difficulties. Suitable conditions for rotational molding of the present composition are illustrated in the examples.
[0100] Example 1
[0101] Polyethylene
[0102] The polyethylenes used in the examples are shown in Table 1.
[0103] PE-1 is SURPASS ® RMs539-UG, NOVA Chemicals. PE-2 is NOVAPOL ® TR-0735-UG, NOVA Chemicals. PE-4 is SCLAIR ® 19A, NOVA Chemicals.
[0104] PE-1 and PE-2 are each examples of "stabilized polyethylenes" suitable for use in the present compositions and methods. PE-1 and PE-2 are also suitable for use in conventional rotational molding methods.
[0105] PE-3 is a substantially non-stabilized polyethylene - as shown in Table 1, it contains no antioxidant. In addition, the flow rate of PE-3 is very low: it has no meaningful I2 (i.e., it does not exhibit a meaningful flow rate as measured by ASTM D1238 at 190°C using a 2.16 kg load) and has a "high load melt index I2" of only 4.5 g / 10 min. 21” (as measured by ASTM D1238 at 190°C using a 21.6 kg load). Also, the average particle size of PE-3 is large (700 microns).
[0106] PE-4 is included for comparison purposes. It has a high load melt index I of 64 g / 10 min. 21 Therefore, PE-4 is easier to "flow" than PE-3 because the I 21 I than PE-3 21 Much higher. However, the I2 of PE-4 is less than 1 g / 10 min (as shown in Table 1). The I2 flow rate of polyethylene used in conventional roto-molding processes is usually higher than this. In summary: the flow rate of PE-4 is lower than the flow rate of polyethylene used in conventional roto-molding processes, but the flow rate is "too high" to be used as the basic non-stabilized polyethylene of the present composition. PE-4 has an average particle size of 600 microns.
[0107] The average particle size was measured by ASTM D1921.
[0108] A series of blends were made using these polyethylenes. The blend compositions are shown in Table 2.
[0109] Table 1
[0110] .
[0111] Both PE-1 and PE-2 are suitable for conventional / typical rotomoulding processes and are suitable as "stabilized polyethylene" for the present technology. PE-1 was prepared using a single-site catalyst; PE-2 was prepared using a conventional Ziegler-Natta catalyst.
[0112] The stabilizer additives added to PE-1 used in these examples are reported below, expressed as weight parts per million ("ppm") based on the weight of polyethylene. For convenience, the trade name of the stabilizer is provided along with a description of the chemical name or Chemical Abstracts Registry Number.
[0113] 1. 250 ppm IRGASTAB™ FS042 (n,n,-di(alkyl)hydroxylamine)
[0114] 2. 450 ppm of DOVERPHOS™ 9228 (diphosphite: CAS Reg. No. 154862-43-8)
[0115] 3. 750 ppm of TINUVIN™ 622 (HALS: CAS Reg. No. 65447-77-0)
[0116] 4. 750 ppm CHIMASSORB™ 944 (HALS: CAS Reg. No. 70624-18-9)
[0117] 5. 750 ppm zinc oxide.
[0118] The stabilizer kit added to PE-2 is similarly described below:
[0119] 1. 500 ppm of IRGANOX™ 1076 (hindered phenol: octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate)
[0120] 2. 1000 ppm of IRGAFOS™ 168 (Phosphite: tris-(2,4-di-tert-butylphenyl) phosphite)
[0121] 3. 1000 ppm of CYASSORB™ 3529 (HALS: CAS Reg. No. 193098-40-7).
[0122] PE-3 has a very low flow rate (the I2 test did not produce meaningful results; the flow rate at 21.6 kg load is 4.5 g / 10 min). It is produced with a chromium-based catalyst. Polyethylene with this flow rate is usually not used in rotomoulding processes (instead, this type of polyethylene is suitable for blow molding). PE-3 does not contain any stabilizer additives - it is unstabilized.
[0123] PE-4 has a relatively low flow rate (less than 1 g / 10 min for I2 and 64 g / 10 min for I 21 ). However, the flow rate of PE-4 is too high to be suitable as the basic non-stabilized polyethylene of the present disclosure. It is produced with a Z / N catalyst. This type of polyethylene is suitable for making membranes. PE-4 contains 300 ppm of a hindered phenol (IRGANOX™ 1010; CAS Reg. No. 6683-19-8) as the only stabilizer.
[0124] Table 2
[0125] (Blend) composition and rotomolding conditions
[0126] Experiment No. composition Cooking Time (minutes) Oven temperature (℃) 1 - C PE-1 100% 18 295 2 90% PE-1 + 10% PE-3 18 295 3 - C 90% PE-1 + 10% PE-4 18 295 4 - C PE-2 100% 22 295 5 90% PE-2 + 10% PE-3 22 295 6 - C 90% PE-2 + 10% PE-4 22 295 7 - C PE-1 100% 23 295 8 90% PE-1 + 10% PE-3 23 295 9 - C 90% PE-1 + 10% PE-4 23 295 10 90% PE-2 + 10% PE-3 26 295 11 - C 90% PE-2 + 10% PE-4 26 295 12 95% PE-1 + 5% PE-3 23 295 13 - C 95% PE-1 + 5% PE-4 23 295 14 - C PE-2 100% 26 295 15 95% PE-2 + 5% PE-3 26 295 16 - C 95% PE-2 + 5% PE-4 26 295
[0127] C = contrast.
[0128] Table 3
[0129] Surface roughness results
[0130] .
[0131] Rotomolded parts were prepared according to the compositions shown in Table 2 in a rotational molding machine sold by Ferry Industries Inc. under the trade name Rotospeed RS3-160. The machine has two arms that rotate about a central axis. Each arm is equipped with a plate that rotates on an axis that is approximately perpendicular to the axis of rotation of the arm. Each plate is equipped with three cast aluminum molds to produce plastic cubes measuring 12.5 inches (31.8 cm) x 12.5 inches x 12.5 inches. When initially filled with a standard charge of about 3.7 kg of polyethylene resin, these molds produce parts with a nominal thickness of about 0.25 inches (0.64 cm).
[0132] A gas furnace capable of providing 2 million British thermal units (Btu) per hour is used to provide hot air that is circulated around the mold by a fan. Generally speaking, the temperature in the closed furnace is maintained at 250°C to 400°C for a specified period of time while the machine rotates its arm (usually at about 8 revolutions per minute (rpm)) and the plate (usually at about 2 rpm). The specific molding conditions for different compositions are reported in Table 2.
[0133] The "cooked parts" are then cooled by opening the oven. Water spray can also be used to promote cooling. The "cook times", rotation speed, temperature and cooling cycles are computer controlled by appropriate software that also includes a data acquisition system.
[0134] Surface roughness
[0135] The parts were cut to provide test specimens. The surface roughness data of the inner and outer surfaces are shown in Table 3.
[0136] Adhesion test
[0137] The test specimens were prepared by applying a 1 inch (2.5 cm) thick layer of polyurethane foam between two sheets of rotomolded polyethylene (prepared in the manner described above).
[0138] The foams were allowed to "condition" at 23°C for 24 hours prior to adhesion testing.
[0139] The specimens were mounted in a tensile testing machine (sold under the trademark Instron 4204) with clamps attached to the two polyethylene layers. The test speed was set to 8 inches per minute. The test was continued until the part failed. The results are reported in Table 4 as "Peel Strength" (in pounds force).
[0140] Table 4
[0141] Adhesion test results
[0142] experiment Average peel strength (lbf) Standard Deviation (lbf) 1 20.4 5.0 2 48.3 5.5 3 25.8 5.9 4 21.0 1.6 5 36.3 10.1 7 0 - 12 70.6 12.5 13 16.8 2.3
[0143] The results show that rotomoulded parts made with conventional polyethylene compositions and with conventional stabilizer packages yielded molded parts that did not adhere well to the polyurethane foam when parts were made according to the rotomoulding conditions of the examples (see Comparative Experiments 1, 4 and 7).
[0144] It was observed that the use of a substantially non-stabilized polyethylene (ie PE-3) with a low flow rate and a large particle size improved / enhanced the surface roughness on the inside of the molded part (inventive experiments 2, 5, 8, 12 and 15 in Table 3).
[0145] Comparative experiments 3-C, 6-C, 9-C, 11-C, 13-C and 16-C (using PE-4 as the minor component) show that the use of polyethylene with a relatively high flow rate is less effective in producing a rough inner surface.
[0146] The adhesion data in Table 4 show that higher surface roughness improves adhesion to polyurethane.
[0147] Finally, while not wishing to be bound by theory, it is speculated that there may be an optimal aging time / temperature condition that maximizes adhesive bonding, as higher temperatures and / or longer aging times may increase the oxidation level of the polyethylene to a greater extent.
[0148] The present technique can "broaden" the molding conditions that provide suitable adhesion strength because - as shown by the data in Table 4 - we have observed that higher surface roughness can be corrected with stronger adhesion.
[0149] We have observed that the interior surfaces of rotomoulded parts prepared according to this method can have carbonyl groups (C=O) detectable by Fourier transform infrared (FTIR) analysis.
[0150] We have also observed that the use of substantially non-stabilised polyethylene with low flow rates and large particle sizes can produce rotomoulded parts with high surface roughness.
[0151] We have observed that polyurethanes adhere well to rough surfaces with carbonyl groups.
[0152] Therefore, while not wishing to be bound by theory, it is believed that:
[0153] 1) The stabilized polyethylene (having a small particle size and high flow rate compared to the substantially non-stabilized polyethylene) melts in the heated mold and preferentially flows to the mold surface, thereby forming the outer surface of the molded part;
[0154] 2) the substantially non-stabilized polyethylene (having large particle size and poor flow rate) does not flow as well to the mold as the stabilized polyethylene, resulting in the presence of the substantially non-stabilized polyethylene on the inner surface of the molded part;
[0155] 3) Large particles of substantially non-stabilized polyethylene together with the poor flow rate of this material contribute to high surface roughness of the inner surfaces of parts prepared according to the present method;
[0156] 4) the substantially non-stabilised polyethylene is partially oxidised during the rotomoulding process, thereby resulting in the formation of oxide species on the inner surface of the part - in particular carbonyl groups (C=O) in sufficient quantities to be observed by FTIR analysis; and
[0157] 5) The combination of A) high surface roughness and B) the presence of carbonyl groups improves the adhesion between the surface of the rotomoulded part and the polyurethane.
[0158] Industrial Applicability
[0159] A rotomoulding composition is provided, which comprises a blend of two polyethylenes: 1) a well-stabilized polyethylene; and 2) a poorly stabilized polyethylene having a very low flow rate. A rotomoulding part made from the composition has a rough inner surface and polyurethane foam adheres well to the rough surface.
Claims
1. A polyethylene composition comprising: 1) 85 to 99 weight percent of a stabilized polyethylene having a melt index I2 of 0.5 to 10 g / 10 min as measured by ASTM D 1238 at 190°C using a 2.16 kg load; a density of 0.920 to 0.950 g / cc as measured by ASTM D792; wherein the stabilized polyethylene is a polyethylene containing a stabilizer package to protect the polyethylene from degradation / oxidation during a rotomoulding process, the stabilizer package comprising a primary antioxidant and a secondary antioxidant; and 2) 15 to 1 wt. % of a substantially non-stabilized polyethylene having (i) a high load melt index I of 2 to 20 g / 10 min as measured by ASTM D 1238 at 190°C using a 21.6 kg load 21 ; (ii) a density of 0.950 to 0.965 g / cc as measured by ASTM D792; and (iii) an average particle size of 500 to 3000 microns; wherein the substantially unstabilized polyethylene contains less than 100 ppm of a primary antioxidant and / or a secondary antioxidant, and wherein the average particle size of the stabilized polyethylene is less than the average particle size of the substantially unstabilized polyethylene.
2. The polyethylene composition of claim 1, wherein the particle size is from 500 to 1000 microns.
3. The polyethylene composition of claim 1, wherein the substantially non-stabilized polyethylene has a high load melt index I of 3 to 6 g / 10 min as measured by ASTM D1238 at 190°C using a 21.6 kg load. 21 .
4. The polyethylene composition according to claim 1, wherein the stabilizer kit for stabilizing polyethylene comprises: 1.1) a primary antioxidant in an amount of 250 to 1500 parts per million by weight, and 1.2) A secondary antioxidant in an amount of 250 to 1500 parts per million by weight.
5. A method for preparing a rotomoulded component, comprising: a) preparing a polyethylene composition according to any one of the preceding claims; and b) subjecting the polyethylene composition to rotational molding. The method according to claim 5 , wherein the rotational molding is performed at a temperature of 250° C. to 400° C.
7. The method of claim 5 which produces a rotomoulded part having an inner surface with a surface roughness of 10 to 30 microns.
8. The method of claim 7, wherein the surface roughness is 12 to 20 microns.
9. The method of claim 7, wherein the interior surface is further characterized by having carbonyl functional groups detectable by Fourier transform infrared instrumentation.
Citation Information
Patent Citations
Polyethylene composition for rotational moulding and preparation method of polyethylene composition
CN102050978A
Rotational moulding foaming polyethylene composite and polyethylene foaming product
CN106554535A